2012
DOI: 10.15835/nbha4017333
|View full text |Cite
|
Sign up to set email alerts
|

Qualities of Native Apple Cultivar Juices Characteristic of Central Europe

Abstract: During the last century due to the changes in landscape management, in country people's lives and with intensive fruit-growing the native cultivars of apple fruit trees have been gradually disappearing. The aim of the study was to compare the juices made of native apple cider cultivars. The cultivars-'Boikovo' , 'Jadernicka moravska' , 'Kardinal zihany' , 'Panenske ceske' , 'Parmena zlata zimni' , 'Strymka' growing in the locality of the Litencicke Hills in the eastern part of the Czech Republic were selected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The determination of antioxidant activity, concurrently with the assessment of the main representative bioactive components in berries–polyphenolic compounds‒is one of the ways of expressing the biological value of the edible honeysuckle berries [31]. Numerous assays have been described to measure various free radical damage products or antioxidant status and the plethora of available techniques attest to the fact that no single ideal method is available [36,37,38]. In addition, levels of antioxidants in food do not necessarily reflect their antioxidant activity [39,40,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…The determination of antioxidant activity, concurrently with the assessment of the main representative bioactive components in berries–polyphenolic compounds‒is one of the ways of expressing the biological value of the edible honeysuckle berries [31]. Numerous assays have been described to measure various free radical damage products or antioxidant status and the plethora of available techniques attest to the fact that no single ideal method is available [36,37,38]. In addition, levels of antioxidants in food do not necessarily reflect their antioxidant activity [39,40,41,42].…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned by many authors [1,46,47] this is a typical trait of the majority of fruit species not only in the case of antioxidant capacity of phenolics, ascorbic acid, but also where it concerns the relationship between phenolics and ascorbic acid and ROS [48,49].…”
Section: Reactive Nitrogen Species Scavenging Activity Assaymentioning
confidence: 99%
“…have recently attracted increasing attention in the field of food nutraceuticals and medicine because of their widely reported health benefits. Recent trials have demonstrated their efficacy in lowering blood cholesterol and in the reduction of the risk of cardiovascular diseases [ 7 , 11 , 12 , 13 ], which can be considered as the most significant among other lesser known fruit species [ 14 , 15 , 16 ]. Nowadays it is also well known that all these mentioned beneficial health promoting activities are connected with polyphenolic compounds and triterpene acids [ 8 ].…”
Section: Introductionmentioning
confidence: 99%